2017
DOI: 10.1007/s11418-017-1104-7
|View full text |Cite|
|
Sign up to set email alerts
|

Naturally occurring Vpr inhibitors from medicinal plants of Myanmar

Abstract: Human immunodeficiency virus type-1 (HIV-1) is a lentiviral family member that encodes the retroviral Gag, Pol, and Env proteins, along with six additional accessory proteins, Tat, Rev, Vpu, Vif, Nef, and Vpr. The currently approved anti-HIV drugs target the Pol and Env encoded proteins. However, these drugs are only effective in reducing viral replication. Furthermore, the drugs’ toxicities and the emergence of drug-resistant strains have become serious worldwide problems. Resistance eventually arises to all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…A CHCl 3 fraction of K. pulchra exhibits Vpr-inhibitory activity at 25l g mL −1 . In addition, isopimarene type diterpenoids isolated from the rhizomes of the plants, kaempulchraol B ( 43 ), kaempulchraol D (45) , kaempulchraol G ( 46 ), kaempulchraol Q ( 20 ), kaempulchraol T ( 36 ), kaempulchraol U ( 50 ), and W ( 22 ) inhibit the expression of Vpr at concentrations from 1.56 to 6.25 µM [25].…”
Section: Biological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A CHCl 3 fraction of K. pulchra exhibits Vpr-inhibitory activity at 25l g mL −1 . In addition, isopimarene type diterpenoids isolated from the rhizomes of the plants, kaempulchraol B ( 43 ), kaempulchraol D (45) , kaempulchraol G ( 46 ), kaempulchraol Q ( 20 ), kaempulchraol T ( 36 ), kaempulchraol U ( 50 ), and W ( 22 ) inhibit the expression of Vpr at concentrations from 1.56 to 6.25 µM [25].…”
Section: Biological Activitymentioning
confidence: 99%
“…The isopimaranes reported from the Kaempheria species (Table 1) are characterized with the presence of two double bonds; one is mostly ∆ 15(16) , while the other is between ∆ 8(9) or ∆ 8(14) [4,25,74]. From the rhizomes of K. galanga , 12 usual isopimarenes ( 1–8 , 10 , 11 , 14 , and 17 ) were observed that contained a ∆ 8(14),15 motif in addition to the rarely reported oxygenated seco-isopimarane ( 56 ) [16].…”
Section: Chemical Metabolites Of Kaempferia Speciesmentioning
confidence: 99%
“…A chemical or peptide, designed to inhibit UNG2 association with Vpr, ought to be detrimental to HIV-1 fitness [100]. It is also noted here, that natural plant extracts acting as general inhibitors of Vpr have been reported [101]. Any general Vpr-inhibiting compounds making it into the clinic would have the potential to compromise HIV-1 viability fairly comprehensively [102].…”
Section: C) Hiv-1mentioning
confidence: 74%
“…1,2) In order to find Vpr inhibitors, we have established an assay system where we developed tetracycline regulated TREx-HeLa-Vpr cells and studied the inhibition effect of compounds on Vpr by monitoring the proliferation rate of cells. 3) By using this assay, we identified a number of natural small molecules including isopimarane diterpenoids, 3,4) quassinoids, 5) iridoid and bis-iridoid glucosides, 6) xanthone, 7) and triterpenoid 7) from medicinal plants of Myanmar as potent Vpr inhibitors. 8) Interestingly, as infectious microorganisms evolve and develop resistance to existing pharmaceuticals, marine sponges provide novel leads against bacterial, fungal, and viral diseases, although the availability of more sensitive and different bioassay systems to date will be needed for drug discovery against these diseases.…”
Section: Introductionmentioning
confidence: 99%